Cerebral perfusion and neurological examination characterise neonatal opioid withdrawal syndrome: a prospective cohort study. Issue 4 (1st November 2021) - Benninger, Kristen L; Peng, Jin; Ho, Mai-Lan; Newton, Julia; Wang, Danny J J; Hu, Houchun H; Stark, Ann R; Rusin, Jerome A; Maitre, Nathalie L
Abstract : Objective: To test the hypothesis that cerebral blood flow (CBF) assessed with arterial spin labelling (ASL) MRI is increased and standardised neurological examination is altered in infants with neonatal opioid withdrawal syndrome (NOWS) compared with those without. Design: Prospective cohort study. Setting: Level IV neonatal intensive care unit and outpatient primary care centre. Participants: Infants with NOWS receiving pharmacological treatment and unexposed controls matched for gestational age at birth and post-menstrual age at MRI. Main outcomes: CBF assessed by ASL on non-sedated 3-Tesla MRI and standardised Hammersmith Neonatal Neurological Examination (HNNE) within 14 days of birth. Results: Thirty infants with NOWS and 31 control infants were enrolled and included in the final analysis. Global CBF across the brain was higher in the NOWS group compared with controls (14.2 mL/100 g/min±5.5 vs 10.7 mL/100 g/min±4.3, mean±SD, Cohen's d=0.72). HNNE total optimality score was lower in the NOWS group compared with controls (25.9±3.6 vs 28.4±2.4, mean±SD, Cohen's d=0.81). A penalised logistic regression model including both CBF and HNNE items discriminated best between the two groups. Conclusions: Increased cerebral perfusion and neurological examination abnormalities characterise infants with NOWS compared with those without intrauterine drug exposure and suggest prenatal substance exposure affects fetal brain development. Identifying neurological and neuroimaging characteristics of infants with NOWS can contribute to understanding mechanisms underlying later outcomes and to designing potential new treatments. Abstract : This prospective cohort study found that 30 infants with neonatal opioid withdrawal syndrome had higher global cerebral blood flow and more neurological exam abnormalities than 31 unexposed controls. Follow-up to determine these infants' neurodevelopmental courses is required.